Stigma in Access to HIV Treatment in African Settings: - Kingsley Oturu (Grounded Theory Review: An International Journal, 2011)
Access to antiretroviral therapy is desperately needed in Nigeria. Increased access to anti-retroviral therapy for HIV treatment contributes to improved quality of life and reduced health care costs. It may assist in reduction of stigma and risk of HIV transmission. Although a lot of global funding has been mobilised to improve access to HIV treatment, many people in Nigeria still do not have access. The HIV treatment access rate in Nigeria is 16.6%. It is often assumed that with the provision of antiretroviral therapy, patients will readily access HIV treatment. However, as this grounded theory (GT) study suggests, stigma stands out as a major barrier to HIV prevention and treatment services in Nigeria. The main concern of the participants that emerged in this GT study was the fear of different types of stigma that stand as barriers to access. Self stigma, familial stigma and community stigma, institutional stigma and organisational stigma surfaced as issues that influence access. The participants were also able to overcome stigma and other barriers to accessing HIV treatment through the use of social connections. Social connection emerges as the core category of this theory. The core determinant to engaging with social connectors is the type of disclosing strategy utilised by the research participants. The social connection theory on access developed from this study suggests that although stigma poses a major barrier to HIV treatment, social connectors can play a major role in supporting the patient in overcoming barriers to access HIV treatment. Social connectors were identified as trusted acquaintances that influenced how and when HIV patients access treatment. I therefore argue in this paper that in African settings, social connectors should be targeted in access programs and not just the individual patient. The theory may be adapted for other diseases associated with stigma, such as leprosy or mental illnesses. It may also be relevant for African patients living in western or non-African contexts or in contexts within developed countries where there is strong social capital.